Selfefficacy and Intrinsic Motivation Dreivers of Entrepreneurial Interest in Mosque in Teenagers in Deli Serdang - Siregar, Dahrul; Simatupang, Dewi Ratna Sari (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2025)
The role of religious institutions in fostering entrepreneurial mindsets among youth has gained increasing attention in recent years. This study examines the intersection of self-efficacy and intrinsic motivation as key drivers of entrepreneurial interest among teenagers participating in mosque activities in Deli Serdang, Indonesia. With a youth population of approximately 25% and over 500 active mosques in the region, Deli Serdang presents a unique opportunity to understand how religious environments influence entrepreneurial development in young people. Research aims to analyze the influence of self-efficacy and intrinsic motivation on interest in entrepreneurship among mosque teenagers in Deli Serdang Regency. Self-efficacy or self-efficacy is a person's belief in his or her ability to carry out a task, while intrinsic motivation is a drive from within that arises because of needs and desires from within oneself. The research used quantitative methods with a survey approach to mosque youth in Deli Serdang Regency. Data collection was carried out through questionnaires distributed to respondents using purposive sampling technique. Data analysis uses multiple linear regression to test the research hypothesis. The research results show that self-efficacy and intrinsic motivation partially and simultaneously have a positive and significant effect on the entrepreneurial interest of mosque teenagers. These findings indicate that increasing self-efficacy and intrinsic motivation can encourage the growth of interest in entrepreneurship among mosque youth. This research provides theoretical contributions to the development of religious community-based entrepreneurship literature and practical implications for the development of mosque youth economic empowerment programs